2011
DOI: 10.1159/000327368
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Infusion of Paclitaxel with In-Line Filters

Abstract: Background: Paclitaxel is one of the most effective anticancer drugs ever developed. To prevent hazards associated with intravenous (IV) administration which include the formation of microbubbles, microbiological contamination and particulate matter, the suppliers recommend that an in-line IV filter should be used during the infusion of the chemotherapeutic agent. Methods: To rule out the possibility that polyethersulfone (PES) membranes retain the paclitaxel during filtration, we carried out specific tests. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Chemical analysis could also determine any interactions between drugs and filter membrane, in relation to drug retention. A limited number of cases concord with this 29 , whereas most studies have revealed no variations in drug concentration when using in-line filters 30 33 . Room temperature should also be taken into account because of its impact on particle formation.…”
Section: Discussionmentioning
confidence: 82%
“…Chemical analysis could also determine any interactions between drugs and filter membrane, in relation to drug retention. A limited number of cases concord with this 29 , whereas most studies have revealed no variations in drug concentration when using in-line filters 30 33 . Room temperature should also be taken into account because of its impact on particle formation.…”
Section: Discussionmentioning
confidence: 82%